Constitutive Relations under Impact Loadings Experiments, Theoretical and Numerical Aspects - Lodygowski, Tomasz; Rusinek, Alexis; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2014)
The book describes behavior of materials (ductile, brittle and composites) under impact loadings and high strain rates. The three aspects: experimental, theoretical and numerical are in the focus of interest. Hopkinson bars are mainly used as experimental devices to describe dynamic behavior of materials. The precise description of experimental techniques and interpretation of wave interaction are carefully discussed. Theoretical background refers to rate dependent thermoviscoplastic formulation. This includes the discussion of well posedness of initial boundary value problems and the solution of the system of governing equations using numerical methods. Explicit time integration is used in computations to solve dynamic problems. In addition, many applications in aeronautic and automotive industries are exposed.
Testing with bars from dynamic to quasi-static -- Dynamic testing of materials -- Material behavior under dynamics loading, modeling and experiments -- Analysis of some high-speed impact problems in the aircraft industry -- Computer estimation of plastic strain localization and failure for large strain rates using viscoplasticity -- Inelastic flow and failure of metallic solids accounting for asymmetry of elastic range and micro-shear banding.
Keywords: Mechanics; Mechanics, Applied; Materials science; Solid Mechanics; Characterization and Evaluation of Materials; Solid Mechanics